Ethics of care and public mental health care: a case study in Barcelona - Jaume Martínez Flores; Margot Pujal i Llombart; Enrico Mora (Instituto de Salud Colectiva, Universidad Nacional de Lanús, 2021)
This article aims to analyze public mental health services in the city of Barcelona from a gender-based perspective. We do so through a case study of mental health services for adults in the context of recent community-oriented and transdisciplinary mental health care reforms. Employing a qualitative methodology, we look at the discourses of mental health professionals regarding the ways in which they approach the therapeutic relationship between professional and user, specifically with reference to vulnerability and proposals for addressing it. Between November 2018 and April 2019 we conducted three discussion groups with professionals and another with a group of female users. Data analysis was guided by a categorical content analysis model. The results show a tendency to understand and address vulnerability from an ethics of care based on a community care model, with differences in the discourses of men and women who participated in the research. We conclude that the community-based model promotes the recovery of users' citizenship, as it is based on a notion of interdependence, in contrast to the hospital-based mental health model.